Bangli Regency Government Communication Strategy in Marketing Kintamani Specialty Arabica Coffee and Community Empowerment - Udayana, I Gusti Bagus; Tantra, I Gusti Lanang Putu; Martini, Ida Ayu Oka; Sari, Desak Made Febri Purnama; Wirajaya, Anak Agung Ngurah Mayun; Vinco, Yeo; Apriliathi, Ni Putu Siska (Formosa Journal of Applied Sciences, 2024)
This research uses a qualitative approach with the theory of communicator credibility. The results of this study are; the communication strategy of the Bangli Regency Government in marketing Kintamani Arabica Coffee is; advertising in events, out-of-town trade missions through ministries, and digital promotions. The credibility of communicators in marketing Kintamani Arabica Coffee is quite good in increasing sales so that Kintamani Arabica Coffee can be famous abroad.The obstacles faced by the Bangli Regency Government in marketing Kintamani Arabica coffee include: (1) Lack of motivation, (2) Low capital, (3) Processing and packaging technology that has not been fully mastered by the government, and others.The Bangli Regency Government empowers the community by utilizing the natural resources it has, providing assistance in the form of direction, socialization, and training.